Degradation analysis of dibenzofuran by rhizospheric bacteria - Najwa Husna binti Sanusi (Kulliyyah of Science, International Islamic Universiti Malaysia, 2017)
Polychlorinated dibenzofuran and polychlorinated dibenzo-p-dioxins (PCDF/Ds) are well known for their strong toxicity and mutagenicity. Contamination by these undesirable compounds has been one of the serious environmental problems, thus has been attracting considerable public attention over the last decades. With the demand for green and cleaner technology for remediation process, there is an increased interest in moving away from conventional technologies towards bioremediation technologies. Rhizospheric zone is a suitable place for harboring bacteria that are capable of utilizing chemical compounds which will be used either to facilitate growth of bacteria or the host plants. Identification of the specific microbial members should allow for better strategies to enhance biodegradation. The main focus of this study is to isolate and identify the rhizospheric associated microbes of lemongrass (Cymbopogon citratus), a plant that commonly available in South East Asia. A total of 68 strains isolated from the rhizospheric soil of lemon grass from 2 different unpolluted sites were characterized. Identification of the isolates based on 16S rRNA gene sequence assigned them as members of the phyla Proteobacteria and Firmicutes, among which those of the genera, Proteobacteria were most abundant. The present study also aimed to find out the capability of microorganisms to utilize dibenzofuran as the sole source of carbon and energy. The dibenzofuran is selected for this study since it is the basic structure for Polyhlorinated dibenzofuran (PCDFs) and a model compound for degradation of PCDFs. Furthermore, dibenzofuran is less toxic compared to its isomeric compounds. The optimization of various growth parameters to achieve optimal degradation rate were also investigated. The optimum conditions to degrade dibenzofuran were obtained at 40 ppm of dibenzofuran, pH 7.0, and temperature of 30◦C. A total of four isolates showing significantly higher degradation potential were selected from fourteen isolates demonstrating substantial growth. They were identified as Enterobacter mori sp., Staphylococcus saprophyticus sp., Chromobacterium sp., and Staphylococcus succinus sp. The strains showed optimum utilization (~90%) of dibenzofuran. It was found that the degradation rates of dibenzofuran by strain Staphylococcus succinus sp., in enrichment culture were approximately 96%, which is the highest and fastest within 24 hours incubation. These results suggest that strain was able to degrade dibenzofuran more efficiently than other strains. To our knowledge, this study is the first report in which Staphylococcus succinus sp., was identified as a dibenzofuran degrader. This study has also investigated the involvement of bph genes in degradation of dibenzofuran by selected bacteria. All the strain from rhizospheric bacteria carried partial bphA genes because all the strain only has <70% similarity of bphA gene. The presented results indicated the potential of these bacterial isolates to be used for in-situ bioremediation of dioxin-like compound which provide an efficient, economical and an ecological alternative remedy.